PERKEMBANGAN MACAPAT DAN KONTRIBUSINYA DALAM KARAWITAN JAWA - Sugimin Sugimin (Gelar : Jurnal Seni Budaya, 2010)
Macapat is a Javanese poem having the following rhymes: guru wilangan (numbers of syllables in every line), guru lagu (vocal of the syllable at the last line), and guru gatra (numbers of lines in  every kind of macapat). Each macapat has a different kind of guru wilangan, guru lagu and guru gatra. These three elements differ one kind of macapat from the others. Serat and Babad in  Javanese literature are written in the form of macapat. These two works of literature are recited in a singing voice. Tembang macapat which firstly had the function of reading has developed and  taken the form of a various musical works such as ketawang, ladrang, palaran, bawa gendhing and gendhing laras madya. The development of the musical work on tembang macapat into a  variety of musical works has something to do with the artist's creativity. In addition to aesthetic demands, the development is caused by the changes of function of musical performance. This  shows that when the society's demand for the use of a work of art changes, it is time for the artist to re-interpret the existing works of art, including macapat.Key words: Javanese poems, reading, creativity, changes, function, rhymes